Papua New Guinea terrestrial vertebrate richness: elevation matters most for all except reptiles - Tallowin, Oliver J.S.; Allison, Allen; Algar, Adam C.; Kraus, Fred; Meiri, Shai (Wiley, 2017)
Aims To examine species richness patterns in Papua New Guinea’s terrestrial vertebrates and test for geographical congruence between the four classes, and between lizard and snake subgroups. To assess the environmental correlates of Papua New Guinean terrestrial-vertebrate richness, and contrast effects of varying analytical resolution and correction for spatial autocorrelation. We predict congruence in the bird, mammal and to a lesser extent amphibian richness, with weak congruence or incongruence between reptiles and the other taxonomic groups. We further predict these patterns will stem from relative or in the case of reptiles dissimilar, correlative trends with environmental predictors such as elevation and temperature. Location Papua New Guinea. Methods Having created and updated distribution maps for reptiles, we compare them with known ranges of amphibians, birds and mammals and generate species richness grids at quarter-, half- and one- degree spatial resolutions. We examine congruence in species richness between vertebrate groups and between reptile subgroups. We employed spreading-dye models to simulate species richness according to eight environmental predictors and one random model. We accounted for spatial autocorrelation in all analyses. Results Papua New Guinean amphibian, bird and mammal species richness are spatially congruent, a trend which strengthens with decreasing spatial resolution. Reptiles and the lizard and snake subgroups reveal remarkably different spatial-richness trends. Elevational predictors, particularly elevational range at coarse resolutions, provide the strongest correlates of species richness. Terrestrial-vertebrate richness increases with elevation, whereas reptile richness decreases. Main conclusions Congruent species richness gradients in Papua New Guinea are observed in most terrestrial vertebrates, except reptiles. Topographic heterogeneity and associated climatic clines promote diversity in most terrestrial vertebrates but appear to strongly constrain reptile diversity. The topographical complexity and climatic stratiﬁcation of tropical mountains clearly present a wealth of opportunities for diversiﬁcation in most terrestrial vertebrate groups. As reptiles are strongly constrained by temperature, tropical mountains present more of a diversiﬁcation barrier for them.